Penerapan Teknologi Fitoremediasi untuk Menghilangkan Kadar COD dan TSS pada Air Buangan Industri Tahu - Muhammad Al Kholif; Ida Istaharoh; Pungut; Joko Sutrisno; Sri Widyastuti (Al-Ard: Jurnal Teknik Lingkungan, 2021)
Tofu industrial wastewater is a contributor to environmental pollution. Wastewater contains high levels of COD and TSS. The purpose of this study was to determine the effectiveness of reducing pollutant loads in tofu liquid waste by using the phytoremediation method using water jasmine (Echinodorus Palaefolius). The initial stage of the research was a preliminary test to determine the initial content of the waste. The acclimatization process is carried out by observing the process of plant growth during the research process. To maximize plant growth, dilution is carried out with various concentrations of 25% wastewater with 75% diluting water and 50% wastewater with 50% diluting water. Sampling was carried out every 12 hours for 5 days. The results showed that the highest effectiveness of COD reduction occurred in RFT 25% with a residence time of 12 hours at 39.83%, while for TSS parameters the highest effectiveness was at RFT 25% with a residence time of 12 hours by 69%.